2016
DOI: 10.1016/j.ecolind.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow Trout diets and macroinvertebrates assemblages responses from watersheds dominated by native and exotic plantations

Abstract: Over the past few decades, land-use changes through conversion of global forest cover to exotic plantations is contributing to both habitat and biodiversity loss and species extinctions. To better understand human influences on ecosystem, we use diet composition from introduced Rainbow Trout Oncorhynchus mykiss as indicator of potential changes in the composition of stream-macroinvertebrates due to land use changes from native to exotic vegetation (eucalyptus plantations) in southern Chile. Water quality varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 44 publications
(62 reference statements)
1
10
0
Order By: Relevance
“…The literature seems to indicate that benthic invertebrates would have a marked gradient in heterogeneity as a function of the gradient in water conditions of the Cautin river ( Figure 1), as in this aspect it is similar to existing descriptions of other Patagonian rivers (Arenas, 1995;Figueroa et al, 2003Figueroa et al, , 2007Figueroa et al, , 2010Figueroa et al, , 2013Fierro et al, 2012Fierro et al, , 2015Fierro et al, , 2016Encina et al, 2017). Previous reports thus indicate that the taxa Plecoptera, Ephemeroptera and Trichoptera larval stages and Aegla are abundant under turbulent flow, associated with a high oxygen concentration and much particulate matter that makes a food source (Oyanedel et al, 2008;Moya et al, 2009).…”
Section: Benthic Communities Under Potentially Native Conditionssupporting
confidence: 80%
See 1 more Smart Citation
“…The literature seems to indicate that benthic invertebrates would have a marked gradient in heterogeneity as a function of the gradient in water conditions of the Cautin river ( Figure 1), as in this aspect it is similar to existing descriptions of other Patagonian rivers (Arenas, 1995;Figueroa et al, 2003Figueroa et al, , 2007Figueroa et al, , 2010Figueroa et al, , 2013Fierro et al, 2012Fierro et al, , 2015Fierro et al, , 2016Encina et al, 2017). Previous reports thus indicate that the taxa Plecoptera, Ephemeroptera and Trichoptera larval stages and Aegla are abundant under turbulent flow, associated with a high oxygen concentration and much particulate matter that makes a food source (Oyanedel et al, 2008;Moya et al, 2009).…”
Section: Benthic Communities Under Potentially Native Conditionssupporting
confidence: 80%
“…Smith), freshwater crabs of the genus Aegla (Leach, 1820), and the southern Chilean river prawn, Samastacus spinifrons (Phillippi, 1882) (De los Ríos-Escalante et al, 2012;Jara, 2013;Rudolph, 2013), and Diptera, Trichoptera and Ephemeroptera larval stages (Figueroa, 2000;Figueroa et al, 2003Figueroa et al, , 2007, many of these groups are currently endangered due to human-induced alterations in their habitats and the introduction of alien salmonids species since 1914 (Golusda, 1907(Golusda, , 1927Barros, 1931;Jara et al, 2006;Encina et al, 2017;Vega et al, 2017). The (introduced) salmonids, specifically, constitute non-selective, active predators (Soto et al, 2006(Soto et al, , 2007Fierro et al, 2012Fierro et al, , 2015Fierro et al, , 2016Piedra et al, 2012;Valdovinos et al, 2012;Vargas et al, 2010Vargas et al, , 2015. Also, some rivers of this kind have undergone alterations in their surrounding drainage basins, viz., through anthropogenic enterprises as agriculture, deforestation, forestatation, growing cities, industry, among others, these new conditions affect the water quality (Kristensen et al, 2009), and, by consequence, also the benthic species that are sensitive to water pollution are affected in their abundance (Figueroa et al, 2003(Figueroa et al, , 2007Tello et al, 2010;Vega et al, 2013Vega et al, , 2017Gorski et al, 2015;Nimptsch et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies report that the stomach contents of salmonids (i.e., Oncorhynchus mykiss and Salmo trutta) contain a diversity of invertebrate prey present in the benthos of nonintervened (hereafter termed "native") basins, thereby reflecting anthropogenic impacts to the basin [26]. Related to this, Fierro et al [6] reported similarities in stomach contents and prey diversity of the benthos in river sections with land use different than in the basin.…”
Section: Indicators Of Aquatic Ecosystem Healthmentioning
confidence: 99%
“…Worldwide, a primary threat to freshwater ecosystems is the rapid changes occurring in land uses (Figure 1), a situation that has intensified over the past decade [5,6]. Most recent land use conversion has been for crop production, which notably impacts proximal ecosystems due to changes over extensive crop areas [7].…”
Section: Introductionmentioning
confidence: 99%
“…Bioindicators of environmental impact based on benthic macroinvertebrates gained special relevance in Europe (Dermott and Pachkevitch, 2012). However, in Chile and South America they are mostly used to assess the ecological condition of rivers (Brand and Miserendino, 2015;Cardoso and Novaes, 2013;Correa-Araneda, 2016;Correa-Araneda et al, 2010;Dedieu et al, 2016;Dos Santos, 2017;Fierro et al, 2016;Figueroa et al, 2003;Kay et al, 2001;Lallement et al, 2014;Luo et al, 2018;Meza-S et al, 2012;Miserendino et al, 2012;Nascimento et al, 2018).…”
Section: Introductionmentioning
confidence: 99%